Changes in climate will modify the geography of crop suitability: agricultural biodiversity can help with adaptation - Lane, A; Jarvis, Andy (2007)
Climate change will cause shifts in areas suitable for cultivation of a wide range of crops. We used current and projected future climate data for ~2055, and the Ecocrop model to predict the impact of climate change on areas suitable for all crops listed in Table 1 of the International Treaty on Plant Genetic Resources for Food and Agriculture and other major staple and cash crops. Most detrimentally affected in terms of reduction of suitable areas for a range of crops will be sub-Saharan Africa and the Caribbean, areas with the least capacity to cope. Conversely, Europe and North America will see an increase in area suitable for cultivation. These regions have the greatest capacity to manage climate change impacts. To minimize the impacts of these climate and other environmental changes, it will be crucial to breed new varieties for improved resistance to abiotic and biotic stresses is. Plant breeders need to increase their attention to breeding varieties that have greater tolerance to local abiotic stresses such as drought, flooding and extreme temperatures as well as continuing to breed for resistance to pests and diseases. Priorities for breeding should consider the magnitude of the predicted impacts on productivity of the crop, the number of people who depend on the crop and their level of poverty, and the opportunities for significant gains through breeding. Local knowledge of ecological interactions, traditional varieties, and the genetic diversity in the wild relatives of domesticated crops provide rich resources on which to build priority breeding programmes for climate change-tolerant varieties.